A novel method for monetary valuation of street trees: a case study in a Brazilian city - Tamara Ribeiro Botelho de Carvalho Maria; Allan Rodrigo Nunho dos Reis; Jennifer Viezzer; Daniela Biondi (Acta Biológica Catarinense, 2023)
Street trees offer numerous ecosystem benefits when well managed by the municipal administration. However, quantifying these benefits is complex, which contributes to the negligence and undervaluation of afforestation by municipal managers and the population as a whole. Thus, the valorization of urban afforestation emerges as a strategic awareness tool, capable of translating the importance of each individual tree within the urban green infrastructure for citizens and municipal managers, in addition to assisting in the process of choosing the best guidelines and practices for urban forest management. When applied to street tree planting, these methods fail to consider the most important aspect of a tree in the urban environment: its canopy. Thus, this research aimed to propose a new method for the monetary valuation of street trees, focusing on the benefits of the canopy and applying this method in a case study. Tree species, condition, location, biometric value and implementation cost were considered. The case study results reached US 600 million, with individual trees between US 213.93 and US 483,615.19. The main limiting factors for the evaluation of the street tree planting were the location of the plating and the low height of the bifurcation. Keywords: ecosystem services; nature economy; tree canopy; tree economic value; urban forest.